2001
DOI: 10.1021/ma0111360
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Copolymerization of Ethylene and Propylene:  Evidence for Selective Chain Transfer to Ethylene

Abstract: C1-symmetric ansa-metallocenes Me2E(Ind)(Flu)ZrCl2 (E ) Si (1) and C (2)), upon activation with methylaluminoxane (MAO), produce atactic alternating ethylene-propylene copolymers (up to 92% EP dyads) with low molecular weight (less than 20K). Quantitative 13 C NMR analysis of copolymer chain ends produced with 2/MAO indicates that the chain initiation/termination process is highly selective to generate a vinylidene as the unsaturated end group (terminating end) and an ethyl group as the saturated end group (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 45 publications
(126 reference statements)
4
32
0
3
Order By: Relevance
“…The stereoselectivity of metallocene 2 in liquid propylene is similar at 0 and 20°C (Table 1); previous studies show that the stereoselectivity decreases modestly with increasing monomer concentration at 20°C. 26,28 These results for 2 are consistent with previously discussed enantiomorphic site control mechanism depicted in Scheme 1, where one of the coordination sites is stereoselective and the other is nonstereoselective. Insertion of propylene at the stereoselective site, followed by "site epimerization" (or backskip) from the nonstereoselective site prior to monomer insertion, leads to multiple insertions at the stereoselective site and a predominance of isotactic stereosequences.…”
Section: Resultssupporting
confidence: 87%
“…The stereoselectivity of metallocene 2 in liquid propylene is similar at 0 and 20°C (Table 1); previous studies show that the stereoselectivity decreases modestly with increasing monomer concentration at 20°C. 26,28 These results for 2 are consistent with previously discussed enantiomorphic site control mechanism depicted in Scheme 1, where one of the coordination sites is stereoselective and the other is nonstereoselective. Insertion of propylene at the stereoselective site, followed by "site epimerization" (or backskip) from the nonstereoselective site prior to monomer insertion, leads to multiple insertions at the stereoselective site and a predominance of isotactic stereosequences.…”
Section: Resultssupporting
confidence: 87%
“…Catalyst 1 has less bulky side groups, which enables b- hydrogen transfer to the ethylene monomer, as discussed above. Fan and Waymouth [8] and Balboni et al [9] have reported that termination in EP copolymerisations take place by b-hydrogen transfer to coordinated ethylene monomers, in particular after an inserted propylene monomer. This termination mechanism may have been operative in our polymerisations as well, but our results are not detailed enough to confirm this statement.…”
Section: Molecular Weightmentioning
confidence: 99%
“…One of the benefits of metallocene catalysts over the commercially widely used Ziegler-Natta catalysts is that they allow modification of the ligand structure and, thereby, of the coordination environment of the metal centre, which is essential for rapid catalyst evolution. [5] Although some studies on the termination mechanisms in EP copolymerisations have been reported, [6][7][8][9][10][11] further research is needed for a clear understanding of the relationship between the structure of the metallocene catalyst and the termination mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…1998年, Jin等人 [45] , Amdt等人 [46] 和Leclerc等人 [47] [45] . 若将桥连 [48] . 将桥连的 -C(CH 3 ) 2 -变为-Si(CH 3 ) 2 -, 茂金属化合物13的催化 活性、 共聚产物的交替度和M n 均有所提高, 分别达到 2.05×10 7 g mol −1 h −1 , 90.4% (EPE+PEP=88%)和12300 g mol −1 [48] .…”
Section: 双茂桥连型茂金属催化剂在催化乙烯/丙烯共聚unclassified
“…若将桥连 [48] . 将桥连的 -C(CH 3 ) 2 -变为-Si(CH 3 ) 2 -, 茂金属化合物13的催化 活性、 共聚产物的交替度和M n 均有所提高, 分别达到 2.05×10 7 g mol −1 h −1 , 90.4% (EPE+PEP=88%)和12300 g mol −1 [48] . 在茚基上增加取代基(化合物14), 由于空 [49] .…”
Section: 双茂桥连型茂金属催化剂在催化乙烯/丙烯共聚unclassified